Consequences of International Financial Reporting Standards Adoption in Africa: Evidence From Foreign Direct Investment - Shuibin Gustave; Gigamon Joseph Prah; Kofi K. Tenkorang (European Scientific Journal, ESJ, 2019)
International Financial Reporting Standards (IFRS) Adoption makes financial reporting transparent by enhancing the comparability and the quality of the financial information which reduces the transaction cost and attract foreign direct investment (FDI). This consequently facilitates the effective economic decisions of investors and other market participants. In light of this, many developing countries, in Africa, have resorted to the mandatory-IFRS adoption to enhance the inflow of foreign capital. The study, therefore, aims at finding out the effect of IFRS adoption on FDI inflows. We investigate whether the adoption of IFRS really enhances the inflow of foreign direct investment in developing countries.We use the Fixed Effect regression model, and the sample consisted of 45 (30 IFRS adopted and 15 IFRS non-adopted) African countries from the period of 2000 to 2017. The evidence from our study shows that the adoption of IFRS leads to increased FDI inflows. Most research on international financial reporting standard and foreign direct investment did not control the time period. By conducting further analysis using the difference-in-difference analysis to control the time period, our results highlighted that FDI inflows is higher after the adoption of IFRS. The increase in the value of FDI is influenced by the time period.